Cyberphysical smart cities infrastructures : optimal operation and intelligent decision making - Amini, M. Hadi; Shafie-khah, Miadreza (John Wiley & Sons, Inc., 2022)
"This book introduces novel algorithms and solutions to real-world problems under the umbrella of cyberphysical systems. It is organized in two sections: the first covers optimization algorithms for large-scale decision-making and the second covers intelligent decision-making in cyberphysical smart cities. The book takes into account new directions in engineering and science by deploying novel efficient algorithms to enhance near-real-time operation of underlying networks and use of peer-to-peer communication. These include the more in-depth study of special issues on deployment of these algorithms to improve the operation of smart cities. The material is presented in a concise and understandable form, taking into account the requirements for technical texts"--